2023
DOI: 10.47836/pjst.31.4.20
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Leaching Losses from Continuous Application of Washed Rice Water on Three Contrasting Soil Textures

Abstract: Washed rice water (WRW) is often used as liquid plant fertilizer. However, there is no study on nutrient leaching of soils due to frequent WRW application. Therefore, a column study was undertaken to evaluate the rate of nutrient leaching losses, nutrient retention, and recovery of elements in leachates of three different soil textures irrigated with WRW. The treatments were 3 soil textures and 2 water types. The treatments were evaluated for 8 weeks, and the soils and leachates were measured biweekly. Factori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Notably, this study tested the combined effects of NPK and R3 (N0.5R3), and their combination resulted in the most favorable outcomes for plant growth and nutrient uptake. However, despite the benefits of WRW, this study also highlighted potential challenges such as the lack of observed carryover effects, likely owing to the vulnerability of liquid WRW to leaching, especially in coarse-textured soils, as observed by [ 56 ]. The findings of this study underscore the importance of considering environmental factors and soil texture when applying liquid fertilizers such as WRW, and suggest that preventive measures, such as surface mulches, would be beneficial for mitigating nutrient leaching losses.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Notably, this study tested the combined effects of NPK and R3 (N0.5R3), and their combination resulted in the most favorable outcomes for plant growth and nutrient uptake. However, despite the benefits of WRW, this study also highlighted potential challenges such as the lack of observed carryover effects, likely owing to the vulnerability of liquid WRW to leaching, especially in coarse-textured soils, as observed by [ 56 ]. The findings of this study underscore the importance of considering environmental factors and soil texture when applying liquid fertilizers such as WRW, and suggest that preventive measures, such as surface mulches, would be beneficial for mitigating nutrient leaching losses.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, the soil texture at this study site was sandy clay with 52% sand and 35% clay ( Table 1 ). [ 56 ] found that the extent of leaching loss from WRW depended on soil texture. Applying 5 mm of WRW daily to a sandy clay loam soil (72% sand; 22% clay) over eight weeks resulted in 13–20% more leaching volume and 21–47% higher nutrient losses, particularly K (due to its high mobility in soils), than silt loam (28% sand; 18% clay) and clay (26% sand; 65% clay) soils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation